2006
DOI: 10.1083/jcb.200511109
|View full text |Cite
|
Sign up to set email alerts
|

LMP4 regulates Tbx5 protein subcellular localization and activity

Abstract: The limb- and heart-specific Tbx5 transcription factor coexpresses with and directly binds to the novel PDZ-LIM domain protein, LMP4. LMP4 is distributed in the cytoplasm associated with the actin cytoskeleton. In the presence of LMP4, Tbx5 shuttles dynamically between the nucleus and cytoplasm and, in a complex with LMP4, localizes to actin filaments. Nuclear and cytoplasmic Tbx5 distribution in developing chicken wings suggests the functional significance of the LMP4–Tbx5 interaction. In primary epicardial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
72
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(79 citation statements)
references
References 58 publications
(103 reference statements)
6
72
1
Order By: Relevance
“…Moreover, T was localized to both the chorionic nuclei and cytoplasm. That T-box proteins are not restricted to the nuclei of cells is becoming increasingly well documented (Bimber et al, in press;Camarata et al, 2006), and adds to the further complexity of this family of proteins.…”
Section: Chorio-allantoic (C-a) Union (4-6-s ∼85 Dpc)mentioning
confidence: 99%
“…Moreover, T was localized to both the chorionic nuclei and cytoplasm. That T-box proteins are not restricted to the nuclei of cells is becoming increasingly well documented (Bimber et al, in press;Camarata et al, 2006), and adds to the further complexity of this family of proteins.…”
Section: Chorio-allantoic (C-a) Union (4-6-s ∼85 Dpc)mentioning
confidence: 99%
“…For example, Keap1, an actin-binding protein, controls the transactivity of Nrf2 by retaining Nrf2 in the cytoplasm (Itoh et al, 1999). LMP-4, which is associated with the actin cytoskeleton, indirectly regulates the transcription of Tbx5 target genes, Fgf10 and ANF, through trapping Tbx5 in the cytoplasm (Camarata et al, 2006). Therefore, it is possible that Sddr sequesters an essential molecule for ES cell differentiation in the cytoskeleton to prevent expression of differentiation-associated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Work with chicken primary epicardial cells revealed that endogenous Tbx5 and LMP4 subcellular localization changes in response to differentiation stimuli (13). While the nature of the signal remains elusive, these in vitro differentiation studies provided the first indications that Tbx5 subcellular localization is not dependent solely on the presence of LMP4 within the cell but, rather, on a regulated event.…”
mentioning
confidence: 88%
“…In transfected cells, coexpression of the cytoplasmic LMP4 induces the relocalization of Tbx5 from the nucleus to the cytoplasm, where the Tbx5-LMP4 complex associates with the actin cytoskeleton (30). In the presence of LMP4, Tbx5 shuttles dynamically between the nucleus and the cytoplasm, thus allowing LMP4 to regulate the nuclear availability of Tbx5 and in turn modulate the transcriptional activity of the protein (13).…”
mentioning
confidence: 99%